2002
DOI: 10.1246/bcsj.75.1333
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct Conversion of Carboxylic Acids into Ketones with Organoboronic Acids Promoted by Anhydride Activators

Abstract: Various carboxylic acids are catalytically converted into ketones on treatment with organoboron compounds in the presence of activators and palladium catalysts. Detailed examination of factors influencing the yield of ketone formation revealed the following characteristics of the reactions: (a) Palladium complexes containing tertiary phosphine ligands, particularly triphenylphosphine and tricyclohexylphosphine, are most effective among the palladium complexes; (b) Dioxane and THF are suitable as the solvent; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 77 publications
0
31
0
4
Order By: Relevance
“…Therefore, activation of carboxylic acids would be an important improvement. Actually, independently both Gooßen [56] and Yamamoto [57] found that carboxylic acids can be converted in the corresponding ketones, usually in good yields on treatment with pyrocarbonates and palladium catalysis. Gooßen put first the conditions to convert anhydrides to ketones [58] and then extended the reaction to carboxylic acid via in situ conversion into anhydrides [56].…”
Section: Miscellaneousmentioning
confidence: 99%
“…Therefore, activation of carboxylic acids would be an important improvement. Actually, independently both Gooßen [56] and Yamamoto [57] found that carboxylic acids can be converted in the corresponding ketones, usually in good yields on treatment with pyrocarbonates and palladium catalysis. Gooßen put first the conditions to convert anhydrides to ketones [58] and then extended the reaction to carboxylic acid via in situ conversion into anhydrides [56].…”
Section: Miscellaneousmentioning
confidence: 99%
“…doi:10.1016/j.jorganchem.2007. 10.051 processes using the cleavage of the C-O bond in carboxylic esters and carboxylic anhydrides [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As another application of the concept of the C-O bond cleavage to give acylpalladium complexes, we have developed a new process to prepare ketones and perfluoroketones by combination of the C-O bond cleavage in carboxylic anhydride with transmetallation with arylboronic acids as arylation reagents, providing with further examples of utility of the process involving the Pd-promoted C-O bond cleavage [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…(5)] 22. 24 Under these conditions, the addition of a small amount of water was found to enhance the reaction rate strongly. …”
Section: Carbonic Acids Anhydrides and Estersmentioning
confidence: 94%
“…An activating agent that leaves just readily separable residues would thus be of some advantage. Di‐( N ‐succinimidyl) carbonate25a as well as dimethyl dicarbonate24, 25b, 26 fulfill this requirement. The former coupling reagent is successful in the presence of electron‐rich trialkyl phosphanes and a base such as sodium carbonate.…”
Section: Carbonic Acids Anhydrides and Estersmentioning
confidence: 99%